Daraga Human Resource Development Center: Creating Changes and Conquering Challenges - Magayanes, Sherwin Q. (Bumi Publikasi Nusantara, 2022)
This study aimed to document and uncover the history, growth, and development of Daraga Human Resource Development Center (DHRDC) specifically its historical background, profile in terms of (a) vision, mission, goals, and objectives; (b) administration; (c) faculty; (d) curriculum and course offerings; (e) enrolment; (f) physical plant and facilities and (g) community extension. The significant contributions of DHRDC to education and economy are the prospects for development of the DHRDC, including (a) vision; (b) administration; (c) employment of graduates; and (d) establishment of linkages. Ultimately, this research proposed a Development Plan.